Knowledge of Family Health Strategy professionals about biological neonatal screening - Ferreira, Marina Queiroz Linares; Silva, Marcela de Andrade Pereira (O Mundo da Saúde, 2023)
Biological neonatal screening, popularly known as “heel prick test”, is a preventive test capable of identifying six diseases in newborns, namely: Phenylketonuria, Congenital Hypothyroidism, Sickle Cell Disease and other haemoglobinopathies, Cystic Fibrosis, Congenital Adrenal Hyperplasia and Biotinidase deficiency. This study aimed to evaluate the knowledge of Family Health Strategy professionals about biological neonatal screening. A descriptive, exploratory and quantitative study was carried out, developed with professionals from the Family Health Strategy team in the Basic Health Units of a municipality in the northwest of the state of Paraná. Data was collected through a form on the Google Forms platform and in printed material, analyzed descriptively using absolute and relative frequencies. It was evidenced that of the 69 professionals surveyed, 39 do not know how to list which diseases the test identifies (56.5%), 28(40.6%) indicated the ideal period as being between the 3rd and 5th day of life; and 20(29%) indicated the period before 48 hours of life, 46 (66.7%) do not feel capable of guiding parents about the test. After the birth of the child, 34(49.3%) professionals did not verify whether the test was performed. It was concluded, therefore, that the knowledge and attitude of professionals from the Family Health Strategy Teams in relation to biological neonatal screening is insufficient, and shows the importance of continuing education, that professionals expand their knowledge and feel safe to guide in relation to the heel prick test effectively.